2009
DOI: 10.1530/eje-08-0770
|View full text |Cite
|
Sign up to set email alerts
|

Does an altered leptin axis play a role in obesity among children and adolescents with classical congenital adrenal hyperplasia due to 21-hydroxylase deficiency?

Abstract: Objective: Congenital adrenal hyperplasia (CAH) patients are at a higher risk to develop obesity. The role of leptin in CAH is still controversial. Our study aimed to evaluate serum levels of leptin, the soluble leptin receptor (sOB-R), and the sOB-R: leptin molar ratios in a cohort of CAH children and adolescents, and their associations with clinical and metabolic parameters. Methods: We studied 51 CAH patients, aged 5.6-19.6 years (median 11.8, nZ30 females) crosssectionally. All patients had genetically pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 43 publications
5
35
1
6
Order By: Relevance
“…Glucocorticoid excess and elevated androgens in females, and decreased testosterone in males, may lead to insulin resistance (43,44), and many reports have demonstrated increased insulin resistance in 21OHD (45). We found normal fasting lipids, glucose, HbA1c and insulin levels and a rather favourable lipid profile in the women with elevated levels of HDL.…”
Section: Discussionsupporting
confidence: 51%
“…Glucocorticoid excess and elevated androgens in females, and decreased testosterone in males, may lead to insulin resistance (43,44), and many reports have demonstrated increased insulin resistance in 21OHD (45). We found normal fasting lipids, glucose, HbA1c and insulin levels and a rather favourable lipid profile in the women with elevated levels of HDL.…”
Section: Discussionsupporting
confidence: 51%
“…Increased total body fat has been described in adults with CAH using dual energy x-ray absorptiometry [21,25,27,28], but no change in body fat distribution has been found [39]. It has been speculated that an increased body weight and fat mass might be due to an altered leptin axis in CAH; however, current findings are not fully conclusive [40,41,42]. …”
Section: Cardiovascular and Metabolic Healthmentioning
confidence: 93%
“…Of the few studies that have explored insulin sensitivity in CAH, most have concluded that CAH patients are indeed characterized by insulin resistance (5)(6)(7)(8)(9)(10)(11). Many different methods have been used to assess insulin sensitivity, but studies using the euglycemic hyperinsulinemic clamp method, the gold standard to assess insulin sensitivity, are lacking.…”
Section: Introductionmentioning
confidence: 99%